BACKUP DATA TRANSMISSION NETWORKS AUTOMATED CONTROL SYSTEM LANDING AIRCRAFT - Zhukov , I. A.; Belsky , K. A. (Problems of Informatization and Control, 2021)
The problems of functioning of the air navigation system in case of failures of the subsystem of data exchange with aircraft are considered. A computational structure and a system for providing backup communication for air vessels are proposed.